TMOD-37. IN VIVO COMPRESSION AND IMAGING FOR CAUSAL STUDIES OF MECHANICAL FORCES IN THE BRAIN. (9th November 2020) - Datta, Meenal; Nia, Hadi; Seano, Giorgio; Roberge, Sylvie; Huang, Peigen; Munn, Lance; Jain, Rakesh
Abstract: Clinicians have long observed the effects of abnormal mechanical forces – edema (fluid pressure) in particular – in brain tumors and the surrounding normal brain tissue. However, it was not previously possible to dissect the direct effects of solid stress (i.e., "mass effect"), a mechanopathology resulting from solid components of the tumor tissue, on the brain from the biological and physiological adverse effects exerted by cancer cells. We recently developed for the first time an in vivo compression device that allows for causal and mechanistic studies that delineate the solid mechanical forces of a tumor growing in the brain from its biological effects. The brain poses a unique anatomical consideration of abnormal mechanical forces due to its physical confinement by the skull. We adapted standard transparent cranial windows normally used for intravital imaging studies in mice to include a tunable screw for controlled and acute or chronic compression and decompression in the brain. This compressive cranial window allows for longitudinal imaging of the surrounding brain tissue (cortex or cerebellum) over time (weeks or months) as the screw is lowered further into the brain tissue to recapitulate tumor growth-induced solid stress. Using this device, we have demonstrated that solid stress is causally linked to vascular and neurological dysfunction in the brain. We have also been able to utilize this preclinical system to screen for effective therapeutic interventions to reduce solid stress-induced neuronal death and improve neurological function. Beyond cancer, this technique can be used to study a variety of diseases or disorders that present with abnormal solid masses in the brain, including cysts and benign growths. Thus, mechanistic studies enabled by the compressive cranial window can elucidate the role of mechanics in brain tumor progression, and reveal novel targets for treatment.